USING FEAR AS PERSUASIVE MESSAGES STRATEGY IN ADVERTISING FOR ROAD SAFETY - Agustinus Rusdianto Berto (Puslitbang Literasi dan Profesi SDM Komunikasi dan Informatika, 2015)
Fear strategy has been widely used to approach and persuade the target audience in various road safety campaign messages in Indonesia. However, the factor of how the message perceived by each individual gives a challenge to the effectiveness of this strategy. This thesis examined the influence of perceiving of fear strategy messages in Korlantas Polri road safety advertisements, which aim to motivate younger audience using its resonances. The causal relationship between the strategy and how the message perceived was analyzed using the EPPM model (extended parallel process model) using path analysis. The data collection carried out on 85 privatevocational high school (SMK) students using the one-shot case study experiment design. The results showed that the perceived threats from the advertisement impacts and motivates the students to follow the recommendations from advertising messages, as mediated by an efficacy message. This only found in a group of students who have the resonance, while the other group who did not have the resonance can only be influenced by the message of efficacy. Keywords: extended parallel process model (EPPM), fear appeal, one-shot case study, resonance, road safety advertising